Biologicals decrease psychological distress, anxiety and depression in severe asthma, despite Covid-19 pandemic. (August 2022) - Patella, Vincenzo; Pelaia, Corrado; Zunno, Roberta; Pelaia, Girolamo
Abstract: Patients with respiratory diseases suffer more from problems of severe psychiatric comorbidity than the general population. Asthma might cause psychiatric disorders and affect patients' quality of life negatively. Previous studies reported that mental disorders prevail in asthmatic patients, causing anxiety, depression, and suicidal risk. The aim of this study is to evaluate in real life the prevalence of psychological comorbidities in asthmatics with severe asthma treated by biologicals (Benralizumab, Mepolizumab, Omalizumab). This study starts with the hypothesis that psychological distress, anxiety, depression and suicidal risk in severe asthma patients decreases if treated by biologicals. This study involves a sample of 90 patients (32 males, 58 females and aged 53.92 ± 15.92) suffering from severe asthma and treated with the biological drugs of Benralizumab, Mepolizumab, Omalizumab during Covid-19 pandemic. At the beginning of the treatment (T0) and after 16 weeks (T1), there have been reported results from both clinical disease control, assessed using the ACT, and psychological disorders, assessed with the PSS, HADS and C-SSRS. In the sample of these patients treated with biologicals for severe asthma, the study reported a significant change in all observed parameters, including asthma control (ACT), stress (PSS), anxiety (HADS-A) and depressive symptoms (HADS-D, despite Covid-19 pandemic. In addition, there was a significant improvement in disease management, perceived stress, anxiety and depressive symptoms after a 16 week treatment for severe asthma, independent from the type of biologic drugs used during the pandemic.